(untitled) (Journal of Technology and Operations Management, 2014)
Lean manufacturing have been widely used by manufacturing companies worldwide. However, low rate of success towards lean manufacturing transformation in many countries had created a cause of concern. Change agent system is a crucial element in lean transition as most of the employees are not familiar with lean work environment, and requires a behavioural and mindset change due to the different expectation for performance and value. This study attempts to investigate the role of change agent in the successful implementation of lean manufacturing. Qualitative case study approach is chosen as it offers a more holistic perspective. Therefore, the aim of this paper is to discuss on developing the research design in answering the research questions. A manufacturing company was selected. The four different methods for gathering data: interviews, observation, documents and focus group will contribute towards the categorization and code development process. This enabled a precise analytic approach to the study, which is an induction of highly specified and valid constructs concerning the knowledge development and conveyance process.